2020
DOI: 10.3389/fphys.2020.00791
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Containing Protein From Selenium-Enriched Spirulina platensis Attenuates High Glucose-Induced Calcification of MOVAS Cells by Inhibiting ROS-Mediated DNA Damage and Regulating MAPK and PI3K/AKT Pathways

Abstract: Hyperglycemia is the main feature of diabetes and may increase the risk of vascular calcification (VC), which is an independent predictor for cardiovascular and cerebrovascular diseases (CCD). Selenium (Se) may decrease the risk of CCD, and previous studies confirmed that Se-containing protein from Se-enriched Spirulina platensis (Se-SP) exhibited novel antioxidant potential. However, the effect of Se-SP against VC has been not investigated. Herein, the protective effect and underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…73 Se-Enriched Spirulina platensis protein (SSPP) could inhibit high-glucose induced calcification damage of MOVAS cells by inhibiting MAPKs and the PI3K/Akt pathway, which indicated that SSPP had potential as an effective treatment for cerebrovascular and cardiovascular diseases. 7 SSPP also could inhibit oxygen-glucose deprivation-induced apoptosis and toxicity of hippocampal neurons by regulating the opening and closing of the mitochondrial permeability transition pore, which demonstrated that SSPP had potential application as an effective preventive treatment for ischemic brain injury. 74 In addition, Zhao, et al also showed that Se-enriched Ganoderma lucidum protein could significantly protect cells from DNA oxidative damage.…”
Section: Bioactivities Of Se-enriched Proteins and Their Hydrolysatesmentioning
confidence: 92%
See 3 more Smart Citations
“…73 Se-Enriched Spirulina platensis protein (SSPP) could inhibit high-glucose induced calcification damage of MOVAS cells by inhibiting MAPKs and the PI3K/Akt pathway, which indicated that SSPP had potential as an effective treatment for cerebrovascular and cardiovascular diseases. 7 SSPP also could inhibit oxygen-glucose deprivation-induced apoptosis and toxicity of hippocampal neurons by regulating the opening and closing of the mitochondrial permeability transition pore, which demonstrated that SSPP had potential application as an effective preventive treatment for ischemic brain injury. 74 In addition, Zhao, et al also showed that Se-enriched Ganoderma lucidum protein could significantly protect cells from DNA oxidative damage.…”
Section: Bioactivities Of Se-enriched Proteins and Their Hydrolysatesmentioning
confidence: 92%
“…Lin et al used optical and fluorescent microscopes to observe the morphology of Se-enriched Spirulina platensis protein; the results showed that Spirulina platensis protein and Spirulina platensis exhibited the same spiral shape, which was attributed to the fact that Se could not affect the morphology of the Spirulina platensis protein. 7 During the process of plant germination, plant seeds can absorb Se from the environment and convert inorganic Se into organic Se-enriched proteins. Liu et al studied the effect of different types of proteins on the accumulation order of Se during Oryza sativa L. germination, and the results indicated the total Se content in protein from low to high was gliadin < globulin < glutenin < albumin.…”
Section: Preparation Of Se-enriched Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another molecular mechanism connecting Se status and vascular calcification was defined in experiments on high glucose-induced mouse aortic VSMCs treated with Se-rich Spirulina platensis extract. The Se-containing extract inhibited ROS production, reduced ROS-mediated DNA damage and attenuated dysfunction of MAPK and PI3K/AKT pathways, thus effectively inhibiting high glucose-induced calcification [59].…”
Section: Se and Vascular Calcificationmentioning
confidence: 99%